2002
DOI: 10.1889/1.1830144
|View full text |Cite
|
Sign up to set email alerts
|

39.4: Large Size FED with Carbon Nanotube Emitter

Abstract: High-luminance triode-structure field-emission-display (FED) panel using carbon nanotubes (CNTs) as emitters was first presented in 1999. [1,2] The demonstrated panel showed a good legibility and excellent luminance. After that, the emission stability in ambient gas was evaluated, and reported in 2000.[3] The toughness against ambient gas suggested that CNT FED would be applicable for a large size display panel. But, the experimental panel revealed the lack of luminous uniformity for actual displays. In IDRC'0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 2 publications
1
36
0
2
Order By: Relevance
“…In contrast to SWCNTs, MWCNTs have shown better emission stability; however, a small field enhancement factor has been attributed to low emission current [13]. Recently, double-walled carbon nanotubes have been studied for this purpose due to high current density with long-term emission stability, but the poor production rate and following purification process of catalysts have been a serious bottleneck [14].…”
Section: Surface Functionalization Of Fwcntsmentioning
confidence: 99%
“…In contrast to SWCNTs, MWCNTs have shown better emission stability; however, a small field enhancement factor has been attributed to low emission current [13]. Recently, double-walled carbon nanotubes have been studied for this purpose due to high current density with long-term emission stability, but the poor production rate and following purification process of catalysts have been a serious bottleneck [14].…”
Section: Surface Functionalization Of Fwcntsmentioning
confidence: 99%
“…The tMWCNTs are known to show better field-emission characteristics than SWCNTs and MWCNTs. Previous studies [8,9] of tMWCNTs showed a high field-enhancement factor, like SWCNTs, with the long-term emission stability comparable to MWCNTs. This indicates that tMWCNTs are as sharp as SWCNTs and as strong as MWCNTs.…”
Section: Resultsmentioning
confidence: 88%
“…Panels with various cold cathode structures have been tried to form in triode-type FEDs using carbon nanofiber cold cathode emitters [7][8][9][10][11][12]. In the cold cathode structures of these FEDs, the ratio of separation between the gate electrode and the cathode to the hole diameter of the gate electrode is 1:1 to 3:20.…”
Section: Fed Structure and Simulation Methodsmentioning
confidence: 99%